Holocene sea-level change and evolution of a mixed coral reef and mangrove system at Iriomote Island, southwest Japan. (1st May 2019) - Yamano, Hiroya; Inoue, Tomomi; Adachi, Hiroshi; Tsukaya, Keisuke; Adachi, Ryota; Baba, Shigeyuki
Abstract: Exposed fossil microatolls and core samples from a coral reef and a mangrove forest at the Yutsun River mouth, Iriomote Island, southwest Japan, reveal the internal structure and temporal changes in the sedimentary processes of a mixed reef–mangrove system. Evidence from the core samples and fossil microatolls suggests sea level reached its present position before 5100 cal yr B.P., and a relative sea-level highstand of 1.1–1.2 m above the present sea level occurred from 5100 to 3600 cal yr B.P. This was followed by a gradual fall in relative sea level. The tectonically corrected sea-level curve indicates a stable sea level after 5100 cal yr BP., with a sea-level highstand of up to 0.4 m between 5100 and 3600 cal yr B.P. A nearshore reef dominated by massive Porites and arborescent Acropora initially developed at 6500–3900 cal yr B.P. Reef development was potentially terminated by relative sea-level fall and sediment discharge from the Yutsun River that affected the backreef environment. An offshore coral reef reached present-day sea level by 1000 cal yr B.P., forming a wave break that enabled the foundation of mangrove forest on the fringing reef after ∼1000 cal yr B.P. The reef development was significantly delayed compared with other coral reefs in the region with similar medium-to high-energy conditions, but it provided a calm environment in the backreef area that allowed the development of mangroves. These features demonstrate the chronology and causal relationship between coral reef and mangrove development under the influence of Holocene sea-level change and river discharge.